Approaches in the utilization of Jatrophacurcas oil as feedstock for biodiesel synthesis: a review - Ishola, Mohammed Nurudeen; Kabbashi, Nassereldeen Ahmed; Alam, Md Zahangir; Mirghani, Mohamed Elwathig Saeed (AENSI Publications, 2014)
Apprehension about environmental degradation and the diminishing reserve of fossil fuel are the major drives toward search for alternative energy source. The most prominent biofuel employed in recent times in ransportation of vehicles and propelling of machinery are biodiesel and bioethanol. The utilization of these liquid fuels has witness unprecedented growth in the last two decades due in part to the growing concern of depletion of fossil fuels and on account of environmental impact of the combustion of fossil fuel. Biodiesel is an alternative fuel similar in properties and performance to conventional or fossil fuel. It is a mixture of fatty acid alkyl esters produced from renewable raw materials such as animal fat which is a solid biomass at room temperature or vegetable oil which is a liquid state material. It is produced via tansesterification of triglycerides with monohydric alcohol usually in the presence of a chemical or biological catalyst. Biodiesel of vegetable oils origin such as Jatrophacurcas oil, possess similar qualities to diesel fuel. Jatrophacurcas oil is nonedible oil which can avoid food-fuel competitiveness. Jatrophacurcas is considered as feedstock due to its non-food property, easy propagation, resistant to drought and high yield generation. Jatrophacurcas alkyl ester (Jatropha biodiesel) has properties close to diesel fuel and its utilization reduces CO2 emission to the atmosphere. Jatrophacurcas oil use in diesel engine faces many problems owing to the viscosity which is caused by its large molecular weight. As a result, reduction of its viscosity is of prime importance and this is achieved through several approaches devised over time. This paper reviews production routes for biodiesel production utilizing Jatrophacurcas as feedstock. High conversion is reported in array of routes for Jatropha biodiesel synthesis.